COMPORTAMIENTO DE LOS INDICADORES DE CONTAMINACIÓN FECAL EN DIFERENTE TIPO DE AGUAS DE LA SABANA DE BOGOTÁ (COLOMBIA) - Claudia Campos-Pinilla; Martha Cárdenas-Guzmán; Adriana Guerrero-Cañizares (Universitas Scientiarum)
The world’s population is growing at such rate that not only the demands for water supply have raised considerably butalso its contamination levels. Residues from domestic and industrial origin have generated environmental problems andpublic health issues. Water contamination coming from domestic origin, shows a higher risk because of the quantity oforganic matter and the presence of pathogenic microorganisms. Due to determinations of these pathogens requiressophisticated laboratories and the techniques used for their detection are very costly and time consuming, it is proposedan alternative technique using bacteria, virus and parasites as faecal indicators, since they exhibit similar behaviour, andtheir determination techniques are a lot simpler, faster and low cost. The objective of the present study is to evaluate theoccurrence, concentration and behaviour of indicators from bacterial origin as faecal coliforms, from viral origin assomatic coliphages and F-specific RNA bacteriophages, and from parasite origin such as helminth eggs, Giardia cystsand Cryptosporidium oocysts. A series of samples were taken at surface, groundwater, drinking water and wastewatertreatment system in the surrounding area of Bogotá (Colombia). The results show the presence of all microbial indicatorsin all water samples, in similar concentrations to those found in different countries with different environments.